Nutritional composition and oil fatty acids of Kundur [Benincasa hispida (Thunb.) Cogn.] seed - Sew, Chang Chew; Mohd Zaini, Nurul Aqilah; Anwar, Farooq; Abdul Hamid, Azizah; Saari, Nazamid (Pakistan Botanical Society, 2010)
The seeds from Kundur [Benincasa hispida (Thunb.) Cogn.], a fruit vegetable plant with high functional properties (especially in medicinal treatment), were analysed for nutritive parameters (dietary fiber, crude protein, crude fat, crude fiber, ash, and energy) and oil fatty acids composition. Proximate analysis of the seeds revealed the total dietary fiber as the principal component, comprising 58.43% of the seed. The contents of crude fat and crude protein were found to be 20.70 and 11.63%, respectively. The extracted Kundur seed oil mainly consisted of linoleic acid (C18:2ω6), accounting for 67.37% of the total fatty acids. Other important fatty acid detected were palmitic (C16:0), oleic (C18:1 cis) and stearic (C18:0) acids with contribution of 17.11, 10.21 and 4.83%, respectively. The fatty acids profile of the tested Kundur seed oil was quite comparable to those of previously reported cucurbitaceae seed oils and some other wholesome oils, revealing that it can be used as a potential seed oil crop.